When Do Laws Matter? National Minimum‐Age‐of‐Marriage Laws, Child Rights, and Adolescent Fertility, 1989–2007. Issue 3 (22nd July 2013) - Kim, Minzee; Longhofer, Wesley; Boyle, Elizabeth Heger; Nyseth Brehm, Hollie
Abstract : Using the case of adolescent fertility, we ask the questions of whether and when national laws have an effect on outcomes above and beyond the effects of international law and global organizing. To answer these questions, we utilize a fixed‐effect time‐series regression model to analyze the impact of minimum‐age‐of‐marriage laws in 115 poor‐ and middle‐income countries from 1989 to 2007. We find that countries with strict laws setting the minimum age of marriage at 18 experienced the most dramatic decline in rates of adolescent fertility. Trends in countries that set this age at 18 but allowed exceptions (for example, marriage with parental consent) were indistinguishable from countries that had no such minimum‐age‐of‐marriage law. Thus, policies that adhere strictly to global norms are more likely to elicit desired outcomes. The article concludes with a discussion of what national law means in a diffuse global system where multiple actors and institutions make the independent effect of law difficult to identify.